Influence of changes in shaft rotational speed of rotary equipment on frequency-domain processing - Y. P. Aslamov; A. P. Aslamov; I. G. Davydov; A. V. Tsurko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Evaluation of the technical condition of rotary equipment by vibration signals is traditionally an important task in the field of its production and maintenance. At the current stage of development increasing the effectiveness of vibration-based diagnostics is achieved by automating the solution of this problem and developing new analysis approaches. The influence of changes in shaft rotational speed of rotary equipment on the quality of frequency-domain processing is analyzed in the article. The results of experiments on test equipment are presented.